2009
DOI: 10.1212/01.wnl.0000345016.33983.e0
|View full text |Cite
|
Sign up to set email alerts
|

Osteopenia and osteoporosis in idiopathic benign positional vertigo

Abstract: Osteopenia/osteoporosis may be associated with idiopathic benign positional vertigo (BPV). The effectiveness of measuring bone mineral densitometry and restoring normal calcium metabolism for preventing recurrences of BPV requires further validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
107
3
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(126 citation statements)
references
References 27 publications
8
107
3
4
Order By: Relevance
“…These studies used bone mineral density (BMD), a measurement of calcium levels in particular bone areas, as an indirect clinical indicator of osteoporosis and demonstrated a clear correlation between BPPV and BMD score. Some of these studies suggested that the occurrence of BPPV might be associated with osteoporosis or osteopenia [11,13,21,33], BPPV recurrence might be clinically predicted by a decreased BMD score [11,32], and medications used to treat osteoporosis or osteopenia might be helpful for preventing the occurrence and recurrence of BPPV [18].…”
Section: Introductionmentioning
confidence: 99%
“…These studies used bone mineral density (BMD), a measurement of calcium levels in particular bone areas, as an indirect clinical indicator of osteoporosis and demonstrated a clear correlation between BPPV and BMD score. Some of these studies suggested that the occurrence of BPPV might be associated with osteoporosis or osteopenia [11,13,21,33], BPPV recurrence might be clinically predicted by a decreased BMD score [11,32], and medications used to treat osteoporosis or osteopenia might be helpful for preventing the occurrence and recurrence of BPPV [18].…”
Section: Introductionmentioning
confidence: 99%
“…The otoconia are in a dynamic state, and calcium and potassium are required to mineralize otoconia and to maintain any turnover in the otolith [26 ,27] . Two mechanisms have been proposed to explain the relationship between BPPV and abnormal calcium metabolism: 1) a disturbed internal structure of the otoconia or their interconnections and attachment to the gelatinous matrix and 2) a reduced capacity to dissolve the dislodged otoconia owing to increased concentration of free calcium in the endolymph, resulting from increased calcium resorption [28,29] .…”
Section: Discussionmentioning
confidence: 99%
“…The otoconia are in a dynamic state, and calcium and potassium are required to mineralize otoconia and to maintain any turnover in the otolith [26 ,27] . Two mechanisms have been proposed to explain the relationship between BPPV and abnormal calcium metabolism: 1) a disturbed internal structure of the otoconia or their interconnections and attachment to the gelatinous matrix and 2) a reduced capacity to dissolve the dislodged otoconia owing to increased concentration of free calcium in the endolymph, resulting from increased calcium resorption [28,29] .To this extent, both the cochlea and labyrinth were found to express crucial genes needed to constitute a Ca 2+ absorption mechanism to maintain low levels of endolymphatic Ca 2+ in order to sustain normal hearing and balance functions [30] . The Ca 2+ absorptive system comprises an apical membrane entry pathway (TRPV5 and TRPV6 channels), a cytosolic Ca 2+ buffer protein (calbindin-D9K and calbindin-D28K), and basolateral Ca 2+ exit pathways (sodium-calcium exchangers -NCX-) and plasma membrane Ca 2+ -ATPases (PMCA) [31] .…”
mentioning
confidence: 99%
“…Considering the high prevalence of vitamin deficiency and the growing body of evidences that links it to diseases, it may be sufficient to form a basis for population wide intervention. Since vitamin D is mainly and easily acquired through the skin under exposure to UVb sunlight, such recommendation may yet be another reason for an active and health lifestyle [20][21][22][23][24][25][26][27][28][29].…”
Section: Critical Summationmentioning
confidence: 99%